Minimizing Delay in Lossless Sequential Data Streaming - Mehrotra, Sanjeev; Li, Jin; Huang, Ying-zong (Proceedings of ICME 2010, 2010)
There is an ongoing explosion of interactive Internet applications. By nature, these applications require responsive client-server data exchange and lossless, in-order delivery. In previous work, we have shown that a hybrid FEC-ARQ protocol which combines sending original data packets with forward error correction (FEC) packets is effective in reducing the latency caused by retransmissions of lost packets. However, the prior scheme only sends FEC packets when there are no original packets pending transmission. In this paper, we further expand the investigation of the hybrid FEC-ARQ protocol and show that sometimes, the transmission latency can be further reduced by preempting original data packets with FEC packets. We have formulated the decision of whether to send new original data packets, FEC packets, or resend original data packets as a transmission policy. An optimal transmission policy is selected to minimize the delay experienced by the application subject to a constraint on the amount of waste. By using this optimal policy, we significantly improve the delay performance over straightforward FEC schemes while controlling the amount of waste due to FEC.